Endovascular Closure of Ascending Aortic Pseudoaneurysm With a Type II Amplatzer Vascular Plug. (May 2014) - De Boo, Diederick W.; Mott, Nigel; Kavnoudias, Helen; Walton, Antony; Lyon, Stuart M.
A 71-year-old man initially presented with an asymptomatic, incidentally detected ascending aortic pseudoaneurysm 25 years following aortic root repair with mechanical aortic valve replacement. This pseudoaneurysm was previously treated with coil embolization but due to coil impaction it reopened 8 years later. Endovascular closure of the pseudoaneurysm was achieved with the off-label use of a type II Amplatzer vascular plug.